Penser le numérique : orientations pédagogiques et préoccupations de recherche en didactique des langues - Thierry Soubrié (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Research in the field of languages and digital technology has been going on for about 50 years. What can be said about it? The question is all the more interesting and relevant to ask since it is customary to point out the non-cumulative nature of research in the field of educational technologies. To answer this question, we have chosen in the first instance to move away from the issue of digital education to look at how authors in the field, through a selection of articles and books, conceptualise digital technologies. To do so, we rely on a theoretical framework that includes three levels of questioning: (1) digital technology and its characteristics, (2) human/non-human coupling, (3) the critical dimension. Secondly, we propose a reflection on the way in which the suggestions, or even pedagogical recommendations and research concerns made by the authors relate to their views on digital technology. The main results of this speculative research are then discussed and presented in a summary table.